Autonomy, rationality and contemporary bioethics - Pugh, J (2014)
Personal autonomy is often lauded as a key value in contemporary bioethics. In this thesis, I aim to provide a rationalist account of personal autonomy that avoids the philosophical flaws present in theories of autonomy that are often invoked in bioethics, and that can be usefully applied to contemporary bioethical issues. I claim that we can understand the concept of autonomy to incorporate two dimensions, which I term the 'reflective' and 'practical' dimensions of autonomy. I suggest that the reflective dimension pertains to the critical reflection that agents must carry out on their motivating desires, in order to be autonomous with respect to them. I begin by rejecting prominent desire-based and historical accounts of this dimension of autonomy, before going on to defend an account based upon a Parfitian analysis of rational desires. Following this analysis of the reflective dimension of autonomy, I argue that autonomy can also be understood to incorporate a practical dimension, pertaining to the agent's ability to act effectively in pursuit of their ends. I claim that recognising this dimension of autonomy more comprehensively reflects the way in which we use the concept of autonomy in bioethics, and makes salient the fact that agents carry out their rational deliberations in the light of their beliefs about what they are able to do. I go on to argue that this latter point means that my account of autonomy can offer a deeper explanation of why coercion undermines autonomy than other prominent accounts. Having considered the prudential value of autonomy in the light of this theoretical analysis, in the latter half of the thesis I apply my rationalist account of autonomy to a number of contemporary bioethical issues, including the use of human enhancement technologies, the nature of informed consent, and the doctor-patient relationship.